Preparation method of composite bone repair material
By combining natural inorganic biobond materials with crosslinked CMCS and DBM gel matrix, the shortcomings in existing jaw defect repair materials in biomechanical and degradation properties are solved, and the effect of providing lasting and stable support and microenvironment during bone defect repair is achieved.
Patent Information
- Application Number
- CN202510023520.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-11
AI Technical Summary
Existing jaw defect repair materials have problems with insufficient biocompatibility, degradation performance, fatigue resistance and damage resistance, and are not easy to degrade in the body or slow degradation speed, which affects bone healing and reconstruction.
The natural inorganic biological bone material is combined with a crosslinked gel matrix of carboxymethyl chitosan (CMCS) and decalcified bone collagen (DBM), and the residue is removed by crosslinking of glutaraldehyde to prepare composite bone repair materials with good biomechanical properties and controllable degradation properties.
It provides a lasting and stable support and microenvironment during bone defect repair, has good biomechanical properties and controllable degradation properties, and promotes bone cell growth and bone healing.
Smart Images

Figure BDA0005232079170000171 
Figure HDA0005232079180000011 
Figure HDA0005232079180000012
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomedical materials, and in particular relates to a method for preparing a composite bone repair material. Background Art
[0002] Natural inorganic biological bone materials are implantable biodegradable medical device materials and are widely used in GBR surgery. They can fill bone defects, occupy the defect and guide bone regeneration. Jaw defect is a common disease in oral and maxillofacial surgery. Jaw defect can be caused by many reasons, such as tumors, inflammation, trauma, congenital malformations, etc. Among them, bone defect caused by tumor resection is the most common.
[0003] At present, the commonly used method for mandibular defect in clinical practice is bone grafting. The sources of grafts include autologous bone, allogeneic bone, xenogeneic bone and various inactive artificial bones. Autologous bone transplantation developed rapidly in the early 20th century. Its biggest advantage is that it does not cause rejection reaction. The biggest problem is that the source is limited, and generally autologous bone transplantation requires additional surgery to obtain transplanted autologous bone, which increases the patient's pain, blood loss, surgical infection rate and additional long-term hospitalization costs. Since the 1980s, allogeneic bone has been widely used in clinical practice. The source of allogeneic bone is still relatively limited, and there are also disadvantages such as immune rejection, late infection, slow healing of transplanted bone, and the possibility of cross-infection, which may cause AIDS, spongiform encephalopathy, and hepatitis. Inactive artificial bones mainly include traditional medical metal materials, polymer materials and some bioceramic materials. They are biologically inert, but they do not bond with tissues when implanted in the body, and are prone to loosening and failure. Bioactive xenogeneic inorganic bone materials have good biocompatibility and bioactivity, can form a strong biological bond with natural bone tissue, and have high strength and wear resistance, corrosion resistance, chemical stability, etc. However, the material has low bending strength and high brittleness, and its fatigue resistance and destructive strength in a physiological environment are not high. It can only be used in situations where it does not bear load or only bears a small pure compressive stress load.
[0004] The development of tissue engineering has led the second generation of bioactive bone repair materials to the third generation of biomaterials, which are biomaterials with induction and cell activation capabilities.
[0005] There are many patent technologies related to composite bone repair materials, which mainly include polymer composite materials and hydroxyapatite composite materials. Hydroxyapatite composite materials are divided into industrial synthesis and biological bone purification according to the source of hydroxyapatite. Polymer composite materials are easy to degrade and completely absorbed after degradation, but they have disadvantages such as poor hydrophilicity, weak cell adsorption ability, insufficient mechanical strength, and easy to cause aseptic inflammation. Industrially synthesized hydroxyapatite composite materials have good biomechanical properties and good biocompatibility, but they are not easy to degrade in the body or the rate is very slow, which can become an obstacle to bone healing and reconstruction in the future.
[0006] The bone repair material disclosed in the invention patent application with the patent application publication number CN 117205372 A is obtained by physically mixing the components. The bonding degree of the components may be destroyed after sterilization, which affects the clinical use effect.
[0007] The invention patent application with the patent application publication number CN 109675117 A generates hydroxyapatite precipitate in collagen solution by chemical synthesis, and then washes and freeze-dries the precipitate. In the reaction process, the degree of complexation and effective binding rate of hydroxyapatite with collagen solution during the generation process cannot be effectively controlled, so it may cause uneven product quality.
[0008] The composite bone preparation methods disclosed in the patent application publication number CN 109954167 A and the patent application publication number CN 115382021A both mix polymer components, but because they are both physically mixed, the composite components are only bound by the viscosity between the substances, and they are all freeze-dried. After freeze-drying, the sample structure may be unstable, collapsed and loose. Summary of the invention
[0009] The purpose of the present invention is to provide a composite bone repair material that has good biomechanics and controllable degradation properties and provides long-lasting and stable support and microenvironment during the bone defect repair process.
[0010] To achieve the above object, the present invention provides a method for preparing a composite bone repair material, comprising the following steps:
[0011] S1. Preparation of natural inorganic biological bone materials:
[0012] S11, cutting the animal tissue, removing the cortical bone to obtain cancellous bone 1, crushing the cancellous bone 1 and placing it in purified water or 0.9% saline and boiling it for 10 to 30 minutes, then rinsing it with purified water, repeating the above operation 2 to 5 times, and then placing it in an oven for drying at a drying temperature of 60 to 100° C. to obtain sample A1;
[0013] S12, placing sample A1 in an oxidant, soaking it for 1 to 5 hours, then rinsing it with purified water, and then drying it in an oven at a temperature of 60 to 100° C. to obtain sample B1;
[0014] S13, placing sample B1 in a 4-10% inorganic alkali solution, and soaking it for 1-5 hours to obtain sample C1;
[0015] S14, after cleaning with purified water, sample C1 is placed in a degreasing agent and ultrasonically treated for 10 to 40 minutes, the waste liquid is discarded, and the above operation is repeated 2 to 5 times to obtain sample D1;
[0016] S15. After sample D1 is washed with purified water, it is placed in an organic alkali solution and boiled for 4 to 8 hours. The waste liquid is discarded and the above operation is repeated 2 to 4 times to obtain sample E1.
[0017] S16, after the sample E1 is stirred and washed with purified water, it is placed in an oven for drying at a drying temperature of 60 to 100° C., and then placed in a calcining furnace for low-temperature calcination at a temperature of 200 to 400° C. for a calcination time of 2 to 8 hours, and then stirred and washed with purified water, and then placed in an oven for drying at a drying temperature of 60 to 100° C. to obtain a natural inorganic biological bone material;
[0018] S2. Preparation of decalcified collagen DBM:
[0019] S21: Cut the animal-derived tissue and remove the cortical bone to obtain cancellous bone II. Crush the cancellous bone II and boil it in purified water or 0.9% saline for 10 to 30 minutes. Rinse it with purified water, repeat the above operation 2 to 5 times, and then dry it in an oven at a drying temperature of 40 to 60°C to obtain sample A2.
[0020] S22: Place sample A2 in a degreasing agent, perform ultrasonic treatment for 10 to 40 minutes, discard the waste liquid, and repeat the above operation 2 to 4 times to obtain sample B2;
[0021] S23: Sample B2 is stirred and washed with purified water and then placed in an oven for drying at a temperature of 40 to 60° C. to obtain sample C2;
[0022] S24: placing sample C2 in an acid solution and soaking it at room temperature for 24 to 48 hours to obtain sample D2;
[0023] S25: After washing sample D2 with purified water, place it in a decalcification solution and soak it at room temperature for 24 to 48 hours to obtain sample E2;
[0024] S26: Wash sample E2 with purified water or phosphate buffer, then place in pepsin solution, and place in a water bath at 37°C for 4-8 hours, filter to remove residue, and retain the filtrate;
[0025] S27: adding sodium chloride to the filtrate while stirring until no milky white flocs are produced, removing the supernatant after standing, adding acetic acid solution dropwise to the solution until the flocs are completely dissolved, placing the solution into a dialysis bag, dialyzing, and then freeze-drying to obtain decalcified bone collagen DBM;
[0026] S3, compound:
[0027] S31: dissolving carboxymethyl chitosan CMCS in a phosphate buffer solution of pH 5.0 to 6.0, and preparing a solution with a concentration of 0.5% to 3% by swelling, homogenizing and stirring, and adding decalcified bone collagen DBM of the same mass as that of carboxymethyl chitosan CMCS to the prepared carboxymethyl chitosan CMCS solution, and stirring thoroughly until uniform;
[0028] S32: adding 0.5% to 5% glutaraldehyde solution to the above solution at a mass ratio of 100:3, refrigerating and standing for 2 to 5 hours to obtain a cross-linked gel, then breaking the cross-linked gel into gel blocks, washing with purified water until neutral, then soaking the gel blocks in 0.5 to 5% sodium borohydride ethanol solution for 1 to 2 hours, then washing with purified water, filtering, and then crushing and homogenizing the gel blocks to prepare a gel matrix;
[0029] S33: adding antibiotic drugs and the prepared natural inorganic biological bone material to the gel matrix, and mixing them evenly so that the weight proportion of the antibiotic drugs is 0.1% to 5%, and the weight proportion of the natural inorganic biological bone material is 60% to 80%, to prepare a composite bone mixed material;
[0030] S34: Filling the composite bone mixture material into a mold to shape it, drying and sterilizing it to obtain a composite bone repair material.
[0031] The oxidant in the aforementioned S12 is one or both of hydrogen peroxide and peracetic acid;
[0032] The inorganic base in S13 is one or a mixture of two or more of sodium hydroxide, potassium hydroxide, sodium carbonate and sodium bicarbonate;
[0033] The degreasing agent in S14 is one or a mixture of two or more of methanol, ethanol, ether, acetone, isopropanol, toluene, xylene, petroleum ether, n-hexane, chloroform and ethyl acetate;
[0034] The organic base in S15 is one or a mixture of two or more of propylamine, ethylenediamine, propylenediamine and ethanolamine.
[0035] The degreasing agent in the aforementioned S22 is one or a mixture of two or more of methanol, ethanol, ether, acetone, isopropanol, toluene, xylene, petroleum ether, n-hexane, chloroform and ethyl acetate;
[0036] The acid solution in S24 is one or a mixture of two or more of hydrochloric acid, malic acid, citric acid, phosphoric acid, tartaric acid and nitric acid;
[0037] The decalcification solution in S25 is an EDTA solution with a pH of 7.2 to 8.0.
[0038] The aforementioned antibiotic drugs are any one of gentamicin, acetylspiramycin, tetracycline, azithromycin, penicillin, streptomycin, ofloxacin, chloramphenicol clindamycin, penicillin-streptomycin, tobramycin and vancomycin, or a mixture of two or more thereof.
[0039] The beneficial effects of the present invention are as follows: the composite bone repair material is formed by mixing natural inorganic biological bone material with gel matrix and antibiotic drugs, wherein the natural inorganic biological bone material is prepared by removing antigens and calcining at low temperature. It has good biomechanics and controllable degradation performance. Its gel matrix includes carboxymethyl chitosan (CMCS) and decalcified bone collagen (DBM), and its preparation process is to remove glutaraldehyde residues after cross-linking with glutaraldehyde and then washing and other treatment methods. The cross-linking process can be controlled by the amount and time of adding cross-linking agent, which helps to slow down the degradation performance of the gel matrix and the internal drug release rate after cross-linking, and improves the adhesion of the gel matrix, so that the gel matrix and biological bone powder are more closely combined, providing a lasting and stable support and microenvironment in the bone defect repair process. The present invention has a simple process, low-cost materials, and can effectively realize industrialization.
[0040] Composite bone repair materials are biological bone purified hydroxyapatite materials, which are obtained by purifying biological bone materials and calcining them at low temperatures. They have good biomechanics and suitable degradation properties, can guide bone cell growth, and provide a good microenvironment for bone defect repair. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 It is a data chart of the cumulative release rate of each in vitro simulated antibiotic drug.
[0042] Figure 2 2 are scanning electron microscope images of samples of various embodiments.
[0043] Figure 3 These are the CT results of animal experiments on beagle tooth extraction sockets in each embodiment, wherein (a), (b) and (c) are the CT results of Example 1, Example 2 and Example 3 at 0 month implantation, respectively; (d) (e) and (f) are the CT results of Example 1, Example 2 and Example 3 at 6 months implantation, respectively. DETAILED DESCRIPTION
[0044] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined purpose, the specific implementation methods, structural features and effects of the present invention are described in detail below in conjunction with the accompanying drawings and embodiments.
[0045] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be noted that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0046] The main components of the extracellular matrix of bone tissue are hydroxyapatite, collagen fibers and glycosaminoglycans. The present invention simulates the extracellular matrix of normal body bone tissue by blending the cross-linked gel matrix of natural inorganic biological bone material, carboxymethyl chitosan (CMCS) and decalcified bone collagen (DBM).
[0047] The main component of natural inorganic biological bone material is hydroxyapatite, which has a three-dimensional porous structure and can provide sufficient space for cell growth. It has good biocompatibility and a certain degree of degradability, which can be controlled by the degree of calcination. The degradability of natural inorganic biological bone material has a continuous guiding role in the process of bone defect repair. With the growth of autologous tissue bone, natural inorganic biological bone material gradually degrades, while providing growth space and corresponding osteogenic factors for bone repair.
[0048] Carboxymethyl chitosan (CMCS) is a water-soluble chitosan derivative with multiple biological activities, good biocompatibility and biodegradability. It can be slowly degraded in the body and eventually generates glucose and is absorbed under the action of lysozyme. CMCS is similar in structure to glycosaminoglycans (GAGs) in the extracellular matrix (ECMs) and has similar biological activities. It can promote the adhesion and functional expression of various cells. It is widely used as an extracellular scaffold for the culture of osteoblasts, chondrocytes, fibroblasts, epidermal cells, Schwann cells, hepatocytes, etc.
[0049] Decalcified bone collagen (DBM) is prepared from animal tissues after decalcification and removal of antigens. It has good biocompatibility and is easily degraded in the body. It is an important component of ECMs, anchoring and supporting cells, providing a suitable microenvironment for cell proliferation and growth, and participating in cell migration, differentiation and proliferation.
[0050] Based on the above theory, carboxymethyl chitosan (CMCS) and decalcified bone collagen (DBM) are cross-linked by glutaraldehyde, and then the residual glutaraldehyde residues are removed by sodium borohydride, and then the sodium borohydride is removed by washing to prepare a gel matrix. The gel matrix is then mixed with natural inorganic biological bone materials and antibiotic drugs, and then dried and sterilized.
[0051] The aforementioned natural inorganic biological bone material is prepared by removing antigens from animal tissues and calcining at low temperature. The gel matrix includes decalcified bone collagen (DBM) and carboxymethyl chitosan (CMCS) obtained by cross-linking with glutaraldehyde. The antibiotic drugs involved include any one or a mixture of two or more of gentamicin, acetylspiramycin, tetracycline, azithromycin, penicillin, streptomycin, ofloxacin, chloramphenicol clindamycin, penicillin-streptomycin, tobramycin, and vancomycin. The animal tissues include bovine femur, bovine sternum, pig femur and pig sternum, and one of them can be selected according to actual needs.
[0052] Based on the above description, the preparation method of the composite bone repair material provided specifically includes the following steps:
[0053] Preparation of natural inorganic bio-bone materials:
[0054] S11: The animal tissue is cut and the cortical bone is removed to obtain cancellous bone. The cancellous bone is crushed and placed in purified water or 0.9% saline and boiled for 10 to 30 minutes, then rinsed with purified water, and the above operation is repeated 2 to 5 times. Then, the bone is placed in an oven for drying at a temperature of 60 to 100°C.
[0055] S12: Place the dried sample in an oxidant and soak it for 1 to 5 hours. Rinse it with purified water and then place it in an oven for drying at a temperature of 60 to 100° C. The oxidant is one or both of hydrogen peroxide and peracetic acid.
[0056] S13: placing the dried sample in a 4-10% inorganic alkali solution and soaking it for 1-5 hours. The inorganic alkali is one or a mixture of two or more of sodium hydroxide, potassium hydroxide, sodium carbonate and sodium bicarbonate.
[0057] S14: The sample treated with inorganic alkali is stirred and washed with purified water, and then placed in a degreasing agent, ultrasonically treated for 10-40 minutes, the waste liquid is discarded, and the above operation is repeated 2 to 5 times. The degreasing agent is one or a mixture of two or more selected from methanol, ethanol, ether, acetone, isopropanol, toluene, xylene, petroleum ether, n-hexane, chloroform and ethyl acetate.
[0058] S15: After the defatted sample is washed with purified water, it is placed in an organic base solution and boiled for 4 to 8 hours, the waste liquid is discarded, and the above operation is repeated 2 to 4 times. The organic base is one or a mixture of two or more of propylamine, ethylenediamine, propylenediamine and ethanolamine.
[0059] S16: After the sample treated with organic alkali is stirred and washed with purified water, it is placed in an oven for drying at a drying temperature of 60 to 100°C. The dried sample is placed in a calcining furnace for low-temperature calcination at a low-temperature calcination temperature of 200 to 400°C for a calcination time of 2 to 8 hours. After the calcined sample is stirred and washed with purified water, it is placed in an oven for drying at a drying temperature of 60 to 100°C. A natural inorganic biological bone material is obtained.
[0060] S17: After crushing and grinding the natural inorganic biological bone material, a biological bone powder with a particle size of less than 1 mm is obtained for later use.
[0061] Preparation of decalcified collagen:
[0062] S21: The animal tissue is cut and the cortical bone is removed to obtain cancellous bone. The cancellous bone is crushed and placed in purified water or 0.9% saline and boiled for 10 to 30 minutes, then rinsed with purified water, and the above operation is repeated 2 to 5 times. Then, the bone is placed in an oven for drying at a temperature of 40 to 60°C.
[0063] S22: placing the dried sample in a degreasing agent, ultrasonically treating it for 10 to 40 minutes, discarding the waste liquid, and repeating the above operation 2 to 4 times. The degreasing agent is one or a mixture of two or more selected from methanol, ethanol, ether, acetone, isopropanol, toluene, xylene, petroleum ether, n-hexane, chloroform and ethyl acetate.
[0064] S23: The defatted sample is stirred and washed with purified water and then placed in an oven for drying at a drying temperature of 40 to 60°C.
[0065] S24: placing the dried sample in an acid solution and soaking it at room temperature for 24 to 48 hours. The acid solution is one or a mixture of two or more of hydrochloric acid, malic acid, citric acid, phosphoric acid, tartaric acid and nitric acid.
[0066] S25: After washing the acid-treated sample with purified water, the sample is placed in a decalcification solution and immersed at room temperature for 24-48 hours. The decalcification solution is an EDTA solution with a pH of 7.2-8.0.
[0067] S26: The decalcified sample is washed with purified water or phosphate buffer, and then placed in a pepsin solution and placed in a water bath at 37° C. for 4 to 8 hours. The pH of the pepsin solution is 1 to 4. The residue is removed by filtration, and the filtrate is retained.
[0068] S27: Add sodium chloride to the filtrate while stirring until no milky white floccules are produced. Remove the supernatant after standing, and add acetic acid solution dropwise to the solution until the floccules are completely dissolved. Put the solution into a dialysis bag and dialyze. After dialysis, freeze-dry to obtain decalcified collagen.
[0069] The gel matrix is prepared by mixing carboxymethyl chitosan CMCS and decalcified bone collagen DBM in equal mass ratio and then cross-linking.
[0070] Composite bone repair material composite process:
[0071] S31: Dissolve CMCS in a phosphate buffer solution with a pH of 5.0 to 6.0, and prepare a solution with a concentration of 0.5% to 3% by swelling, homogenization, and stirring. Add DBM in an amount equal to that of CMCS to the prepared CMCS solution, and stir thoroughly until uniform.
[0072] S32: Add 0.5% to 5% glutaraldehyde solution to the above solution at a mass ratio of 100:3, and refrigerate for 2 to 5 hours. Break the cross-linked gel into small pieces, wash with purified water until neutral, soak the gel pieces in 0.5 to 5% sodium borohydride ethanol solution for 1-2 hours, wash with purified water, filter, and then crush and homogenize the gel pieces to prepare a gel matrix.
[0073] S33: Add antibiotics and the prepared natural inorganic biological bone material into the gel matrix and mix them evenly so that the proportion of antibiotics is 0.1% to 5% and the proportion of natural inorganic biological bone material is 60% to 80%.
[0074] S34: Fill the composite bone repair material obtained in S33 into a mold, shape it, dry it, and sterilize it to obtain a final product.
[0075] The preparation method of the composite bone repair material is now described in detail through the following examples.
[0076] Embodiment 1:
[0077] Preparation of natural inorganic bio-bone materials:
[0078] S11: Slice the bovine femur, remove the cortical bone to obtain cancellous bone. After crushing the cancellous bone, boil it in purified water for 30 minutes, rinse it with purified water, and repeat the above operation 3 times. Then, dry it in an oven at a drying temperature of 80°C.
[0079] S12: Place the dried sample in 3% hydrogen peroxide and soak for 1 hour, rinse with purified water, and then place in an oven for drying at a temperature of 80°C.
[0080] S13: Place the dried sample in a 4% sodium hydroxide solution and soak it for 1 hour.
[0081] S14: After the sample treated with inorganic alkali is washed with purified water, it is placed in an acetone / isopropanol mixed solution with a weight ratio of 1:4, and ultrasonically treated for 30 minutes. The waste liquid is discarded, and the above operation is repeated 3 times.
[0082] S15: Place the defatted sample in a 75% ethylenediamine solution, boil at 110°C for 8h, discard the waste liquid, and repeat the above operation 3 times.
[0083] S16: The deproteinized sample is stirred and washed with purified water and then placed in an oven for drying at a drying temperature of 60°C. The dried sample is placed in a calcining furnace for low-temperature calcination at a low-temperature calcination temperature of 200°C for 4 hours. The calcined sample is stirred and washed with purified water and then placed in an oven for drying at a drying temperature of 60°C. A natural inorganic biological bone material is obtained.
[0084] S17: After crushing and grinding the natural inorganic biological bone material, a biological bone powder with a particle size of less than 1 mm is obtained for later use.
[0085] Preparation of decalcified collagen:
[0086] S21: Slice the bovine femur, remove the cortical bone to obtain cancellous bone. Crush the cancellous bone and boil it in purified water for 30 minutes, then rinse it with purified water, and repeat the above operation 3 times. Then place it in an oven to dry at a drying temperature of 40°C.
[0087] S22: Place the dried sample in a mixed solution of acetone / isopropanol in a weight ratio of 1:4, ultrasonically treat for 30 minutes, discard the waste liquid, and repeat the above operation 3 times.
[0088] S23: The defatted sample is stirred and washed with purified water and then placed in an oven for drying at a drying temperature of 40°C.
[0089] S24: Place the dried sample in a 1% hydrochloric acid solution and soak it at room temperature for 24 hours, and then place it in a 5% phosphoric acid solution and soak it in a sealed container at room temperature for 24 hours.
[0090] S25: After washing the acid-treated sample with purified water, the sample was placed in an EDTA decalcification solution with a pH of 8.0 and immersed at room temperature for 48 hours.
[0091] S26: The decalcified sample is washed with purified water, and then placed in a pepsin solution with a pH of 2.4, and placed in a water bath at 37°C for 4 hours. The residue is removed by filtration, and the filtrate is retained.
[0092] S27: Add sodium chloride to the filtrate while stirring until no milky white floccules are produced. Remove the supernatant after standing, and add acetic acid solution dropwise to the solution until the floccules are completely dissolved. Put the solution into a dialysis bag and dialyze. After dialysis, freeze-dry to obtain decalcified collagen.
[0093] The composite bone repair material compounding process is as follows:
[0094] S31: dissolving carboxymethyl chitosan CMCS in a phosphate buffer solution of pH 5.0-6.0, and preparing a solution with a concentration of 1% by swelling, homogenization and stirring. Adding DBM in an amount equal to that of CMCS to the prepared CMCS solution, and stirring thoroughly until uniform.
[0095] S32: Add 0.5% glutaraldehyde solution to the above solution at a mass ratio of 100:3, and refrigerate for 2 hours. Break the cross-linked gel into small pieces, wash with purified water until neutral, soak the gel pieces in 0.5% sodium borohydride ethanol solution for 1 hour, wash with purified water, filter, and then crush and homogenize the gel pieces to prepare a gel matrix.
[0096] S33: Add antibiotics and the prepared natural inorganic biological bone material into the gel matrix and mix them evenly so that the proportion of antibiotics is 0.1% and the proportion of natural inorganic biological bone material is 60%.
[0097] S34: Fill the obtained composite bone repair material into a mold to shape it, and then perform freeze drying and EO sterilization.
[0098] Embodiment 2:
[0099] Preparation of natural inorganic bio-bone materials:
[0100] S11: Slice the pig femur, remove the cortical bone to obtain cancellous bone. After the cancellous bone is crushed, place it in 0.9% saline and boil it for 30 minutes, then rinse it with purified water, and repeat the above operation 3 times. Then place it in an oven to dry at a drying temperature of 100°C.
[0101] S12: Place the dried sample in 3% hydrogen peroxide and soak for 1 hour, rinse with purified water, and then place in an oven for drying at a drying temperature of 100°C.
[0102] S13: Place the dried sample in an 8% sodium carbonate solution and soak for 5 hours.
[0103] S14: After the sample treated with inorganic alkali is washed with purified water, it is placed in a methanol / chloroform mixed solution with a weight ratio of 1:1, and ultrasonically treated for 40 minutes. The waste liquid is discarded, and the above operation is repeated 5 times.
[0104] S15: After cleaning with purified water, the defatted sample is placed in an 80% ethylenediamine solution and boiled at 110° C. for 4 h. The waste liquid is discarded and the above operation is repeated 3 times.
[0105] S16: The deproteinized sample is stirred and washed with purified water and then placed in an oven for drying at a drying temperature of 100°C. The dried sample is placed in a calcining furnace for low-temperature calcination at a low-temperature calcination temperature of 250°C for 2 hours and 400°C for 1 hour. The calcined sample is stirred and washed with purified water and then placed in an oven for drying at a drying temperature of 100°C. A natural inorganic biological bone material is obtained.
[0106] S17: After crushing and grinding the natural inorganic biological bone material, a biological bone powder with a particle size of less than 1 mm is obtained for later use.
[0107] Preparation of decalcified collagen:
[0108] S21: Slice the pig femur, remove the cortical bone to obtain cancellous bone. Crush the cancellous bone, boil it in 0.9% saline for 30 minutes, rinse it with purified water, and repeat the above operation 3 times. Then, dry it in an oven at 60°C.
[0109] S22: Place the dried sample in a methanol / chloroform mixed solution with a weight ratio of 1:1, ultrasonically treat for 40 minutes, discard the waste liquid, and repeat the above operation 3 times.
[0110] S23: The defatted sample is stirred and washed with purified water and then placed in an oven for drying at a drying temperature of 60°C.
[0111] S24: Place the dried sample in a 5% phosphoric acid solution and immerse it in a sealed container at room temperature for 48 hours.
[0112] S25: After the acid-treated sample is washed with purified water, it is placed in EDTA decalcification solution with a pH of 7.2 and immersed at room temperature for 48 hours.
[0113] S26: The decalcified sample was washed with purified water, and then placed in a pepsin solution at pH 4.0 and placed in a water bath at 37°C for 4 hours. The residue was removed by filtration, and the filtrate was retained.
[0114] S27: Add sodium chloride to the filtrate while stirring until no milky white floccules are produced. Remove the supernatant after standing, and add acetic acid solution dropwise to the solution until the floccules are completely dissolved. Put the solution into a dialysis bag and dialyze. After dialysis, freeze-dry to obtain decalcified collagen.
[0115] The composite bone repair material compounding process is as follows:
[0116] S31: Dissolve CMCS in a phosphate buffer solution of pH 5.0-6.0, and prepare a solution with a concentration of 2% by swelling, homogenization and stirring. Add DBM of the same mass as CMCS to the prepared CMCS solution, and stir thoroughly until uniform.
[0117] S32: Add 5% glutaraldehyde solution to the above solution at a mass ratio of 100:3, and refrigerate for 5 hours. Break the cross-linked gel into small pieces, wash with purified water until neutral, soak the gel pieces in 1% sodium borohydride ethanol solution for 2 hours, wash with purified water, filter, and then crush and homogenize the gel pieces to prepare a gel matrix.
[0118] S33: Add antibiotics and the prepared natural inorganic biological bone material into the gel matrix and mix them evenly so that the proportion of antibiotics is 0.1% and the proportion of natural inorganic biological bone material is 80%.
[0119] S34: Filling the obtained composite bone repair material into a mold to shape it, and performing natural drying and irradiation sterilization.
[0120] Embodiment 3:
[0121] The preparation process of natural inorganic bio-bone materials is as follows:
[0122] S11: Slice the pig femur, remove the cortical bone to obtain cancellous bone. After crushing the cancellous bone, boil it in purified water for 30 minutes, rinse it with purified water, and repeat the above operation 5 times. Then, dry it in an oven at a drying temperature of 110°C.
[0123] S12: Place the dried sample in 5% peracetic acid and soak for 1 hour, rinse with purified water, and then place in an oven for drying at a temperature of 110°C.
[0124] S13: Place the dried sample in 8% sodium hydroxide solution at a constant temperature of 80° C. and soak for 30 minutes.
[0125] S14: The sample treated with inorganic alkali is stirred and washed with purified water, placed in an isopropanol mixed solution, and ultrasonically treated for 15 minutes, the waste liquid is discarded, and the above operation is repeated 3 times.
[0126] S15: Place the defatted sample in 80% propylene diamine solution, boil at 110°C for 2h, discard the waste liquid, and repeat the above operation 4 times.
[0127] S16: The deproteinized sample is stirred and washed with purified water and then placed in an oven for drying at a drying temperature of 110°C. The dried sample is placed in a calcining furnace for low-temperature calcination at a low-temperature calcination temperature of 300°C for 3 hours. The calcined sample is stirred and washed with purified water and then placed in an oven for drying at a drying temperature of 110°C. A natural inorganic bio-bone material is obtained.
[0128] S17: After crushing and grinding the natural inorganic biological bone material, a biological bone powder with a particle size of less than 1 mm is obtained for later use.
[0129] The preparation process of decalcified collagen is as follows:
[0130] S21: Slice the pig femur, remove the cortical bone to obtain cancellous bone. Crush the cancellous bone, boil it in 0.9% saline for 10 minutes, rinse it with purified water, and repeat the above operation 3 times. Then, dry it in an oven at 50°C.
[0131] S22: Place the dried sample in an isopropanol solution, perform ultrasonic treatment for 30 min, discard the waste liquid, and repeat the above operation 3 times.
[0132] S23: The defatted sample is stirred and washed with purified water and then placed in an oven for drying at a drying temperature of 50°C.
[0133] S24: Place the dried sample in a 1% citric acid solution and soak it at room temperature for 48 hours.
[0134] S25: After the acid-treated sample is washed with purified water, it is placed in EDTA decalcification solution with a pH of 7.6 and immersed at room temperature for 48 hours.
[0135] S26: The decalcified sample was washed with purified water, and then placed in a pepsin solution at pH 3.5 and placed in a water bath at 37°C for 6 hours. The residue was removed by filtration, and the filtrate was retained.
[0136] S27: Add sodium chloride to the filtrate while stirring until no milky white floccules are produced. Remove the supernatant after standing, and add acetic acid solution dropwise to the solution until the floccules are completely dissolved. Put the solution into a dialysis bag and dialyze. After dialysis, freeze-dry to obtain decalcified collagen.
[0137] The composite bone repair material compounding process is as follows:
[0138] S31: Dissolve CMCS in a phosphate buffer solution of pH 5.0-6.0, and prepare a solution with a concentration of 0.5% by swelling, homogenization and stirring. Add DBM of the same mass as CMCS to the prepared CMCS solution, and stir thoroughly until uniform.
[0139] S32: Add 2.5% glutaraldehyde solution to the above solution at a mass ratio of 100:3, and refrigerate for 4 hours. Break the cross-linked gel into small pieces, wash with purified water until neutral, soak the gel pieces in 1% sodium borohydride ethanol solution for 2 hours, wash with purified water, filter, and then crush and homogenize the gel pieces to prepare a gel matrix.
[0140] S33: Add antibiotics and the prepared natural inorganic biological bone material into the gel matrix and mix them evenly so that the proportion of antibiotics is 0.1% and the proportion of natural inorganic biological bone material is 70%.
[0141] S34: Filling the obtained composite bone repair material into a mold to shape it, and then freeze-drying and irradiation sterilizing it.
[0142] Mechanical property test: The prepared dry sample was placed on a mechanical testing machine, compressed at 50 mm / min, and the maximum bearing force was recorded. The mechanical test results of each embodiment are shown in the following table.
[0143]
[0144] From the above table, it can be seen that the mechanical test results of each embodiment are not much different. The bearing capacity of the composite bone repair material involved in the present invention in clinical application mainly comes from the food contact force during oral chewing and the licking force of the tongue. The mechanical properties of each embodiment can meet the clinical force requirements.
[0145] Drug release rate: The antibiotic content in each example sample was detected respectively. 0.1 g of each example sample was accurately weighed and placed in 50 ml of phosphate buffer with a pH of 7.2. The samples were observed in a 37°C water bath for 90 days, and the antibiotic content was detected. The cumulative drug release rate was calculated. The final test results are as follows: Figure 1 shown.
[0146] from Figure 1 It can be seen that the cumulative drug release rates of each embodiment are similar and have no significant difference. The cumulative drug release rates of each embodiment in the in vitro simulation within 7 days are less than 25%, and the cumulative drug release rates of each embodiment within 90 days are less than 35%, indicating that the drug release can achieve a sustained release effect.
[0147] Scanning electron microscopy was performed on each sample, and the results were as follows: Figure 2 It can be seen that the natural inorganic biological bone material and the gel matrix in each example are tightly combined, so each sample has good mechanical properties.
[0148] The effectiveness test of beagle dog tooth extraction socket was carried out for each embodiment. The CT results of the tooth extraction socket at 0 month (a, b, c) and 6 months (d, e, f) after implantation are as follows: Figure 3 As shown, from the CT scan at month 0, it can be seen that the samples of each embodiment have good space occupation and support. After 6 months of implantation, the samples of each embodiment have been degraded, and new bone has been generated. The overall proportion and support performance of the samples are still retained, which can meet the needs of the clinical recovery period.
Claims
1. A method for preparing a composite bone repair material, characterized in that: The following steps are included: S1. Preparation of natural inorganic biological bone materials: S11, cutting the animal tissue, removing the cortical bone to obtain cancellous bone 1, crushing the cancellous bone 1 and placing it in purified water or 0.9% saline and boiling it for 10 to 30 minutes, then rinsing it with purified water, repeating the above operation 2 to 5 times, and then placing it in an oven for drying at a drying temperature of 60 to 100° C. to obtain sample A1; S12, placing sample A1 in an oxidant, soaking it for 1 to 5 hours, then rinsing it with purified water, and then drying it in an oven at a temperature of 60 to 100° C. to obtain sample B1; S13, placing sample B1 in a 4-10% inorganic alkali solution, and soaking it for 1-5 hours to obtain sample C1; S14, after cleaning with purified water, sample C1 is placed in a degreasing agent and ultrasonically treated for 10 to 40 minutes, the waste liquid is discarded, and the above operation is repeated 2 to 5 times to obtain sample D1; S15. After sample D1 is washed with purified water, it is placed in an organic alkali solution and boiled for 4 to 8 hours. The waste liquid is discarded and the above operation is repeated 2 to 4 times to obtain sample E1. S16, after the sample E1 is stirred and washed with purified water, it is placed in an oven for drying at a drying temperature of 60 to 100° C., and then placed in a calcining furnace for low-temperature calcination at a temperature of 200 to 400° C. for a calcination time of 2 to 8 hours, and then stirred and washed with purified water, and then placed in an oven for drying at a drying temperature of 60 to 100° C. to obtain a natural inorganic biological bone material; S2. Preparation of decalcified collagen DBM: S21: Cut the animal-derived tissue and remove the cortical bone to obtain cancellous bone II. Crush the cancellous bone II and boil it in purified water or 0.9% saline for 10 to 30 minutes. Rinse it with purified water, repeat the above operation 2 to 5 times, and then dry it in an oven at a drying temperature of 40 to 60°C to obtain sample A2. S22: Place sample A2 in a degreasing agent, perform ultrasonic treatment for 10 to 40 minutes, discard the waste liquid, and repeat the above operation 2 to 4 times to obtain sample B2; S23: Sample B2 is stirred and washed with purified water and then placed in an oven for drying at a temperature of 40 to 60° C. to obtain sample C2; S24: placing sample C2 in an acid solution and soaking it at room temperature for 24 to 48 hours to obtain sample D2; S25: After washing sample D2 with purified water, place it in a decalcification solution and soak it at room temperature for 24 to 48 hours to obtain sample E2; S26: Wash sample E2 with purified water or phosphate buffer, then place in pepsin solution, and place in a water bath at 37°C for 4-8 hours, filter to remove residue, and retain the filtrate; S27: adding sodium chloride to the filtrate while stirring until no milky white flocs are produced, removing the supernatant after standing, adding acetic acid solution dropwise to the solution until the flocs are completely dissolved, placing the solution into a dialysis bag, dialyzing, and then freeze-drying to obtain decalcified bone collagen DBM; S3, compound: S31: dissolving carboxymethyl chitosan CMCS in a phosphate buffer solution of pH 5.0 to 6.0, and preparing a solution with a concentration of 0.5% to 3% by swelling, homogenizing and stirring, and adding decalcified bone collagen DBM of the same mass as that of carboxymethyl chitosan CMCS to the prepared carboxymethyl chitosan CMCS solution, and stirring thoroughly until uniform; S32: adding 0.5% to 5% glutaraldehyde solution to the above solution at a mass ratio of 100:3, refrigerating and standing for 2 to 5 hours to obtain a cross-linked gel, then breaking the cross-linked gel into gel blocks, washing with purified water until neutral, then soaking the gel blocks in 0.5 to 5% sodium borohydride ethanol solution for 1 to 2 hours, then washing with purified water, filtering, and then crushing and homogenizing the gel blocks to prepare a gel matrix; S33: adding antibiotic drugs and the prepared natural inorganic biological bone material to the gel matrix, and mixing them evenly so that the weight proportion of the antibiotic drugs is 0.1% to 5%, and the weight proportion of the natural inorganic biological bone material is 60% to 80%, to prepare a composite bone mixed material; S34: Filling the composite bone mixture material into a mold to shape it, drying and sterilizing it to obtain a composite bone repair material.
2. The preparation method according to claim 1, characterized in that: The oxidant in S12 is one or both of hydrogen peroxide and peracetic acid; The inorganic base in S13 is one or a mixture of two or more of sodium hydroxide, potassium hydroxide, sodium carbonate and sodium bicarbonate; The degreasing agent in S14 is one or a mixture of two or more of methanol, ethanol, ether, acetone, isopropanol, toluene, xylene, petroleum ether, n-hexane, chloroform and ethyl acetate; The organic base in S15 is one or a mixture of two or more of propylamine, ethylenediamine, propylenediamine and ethanolamine.
3. The preparation method according to claim 1 or 2, characterized in that: The degreasing agent in S22 is one or a mixture of two or more of methanol, ethanol, ether, acetone, isopropanol, toluene, xylene, petroleum ether, n-hexane, chloroform and ethyl acetate; The acid solution in S24 is one or a mixture of two or more of hydrochloric acid, malic acid, citric acid, phosphoric acid, tartaric acid and nitric acid; The decalcification solution in S25 is an EDTA solution with a pH of 7.2 to 8.
0.
4. The preparation method according to claim 1 or 2, characterized in that: The antibiotic drug is any one of gentamicin, acetylspiramycin, tetracycline, azithromycin, penicillin, streptomycin, ofloxacin, chloramphenicol clindamycin, penicillin-streptomycin, tobramycin and vancomycin, or a mixture of two or more thereof.
Citation Information
Patent Citations
Composite bone repairing material and preparation method thereof
CN109675117A
Bone repair material and application thereof
CN109954167A
Composite artificial cartilage scaffold and preparation method thereof
CN115382021A
Active bone repair material as well as preparation method and application thereof
CN117205372A